Maschinen und Anlagen auf dem Weg zu Cyber-Physical Systems - Westermann, Thorsten; Iwanek, Peter; Dumitrescu, Roman (19. IFF-Wissenschaftstage: Kooperation im Anlagenbau)

Systematic Business Model Implementation - From Concepts to Real Business - Echterhoff, Benedikt; Gausemeier, Jürgen; Hirschter, Tobias (Proceedings of the 27th ISPIM Innovation Conference, 19. - 22. Jun. 2016 International Society for Professional Innovation Management (ISPIM))
Nowadays business model innovation has become a task, every company has to face in order to stay competitive. Even though, good business concepts are created every day, only few of them make their way from paper to real business. This is mostly due to barriers during implementation: How do we validate our business model? How do we derive requirements and measures? In which way can we keep internal resistance to a minimum? Even though the literature on business model innovation is extensive, business model implementation is covered seldomly. The paper at hand presents a methodology for systematic business model implementation. Key components are a maturity model for business concept validation, an impact analysis for the identification of requirements as well as master plan of action which serves as a communication strategy.

Future-oriented consolidation of product portfolios – Create space for innovations - Dülme, Christian; Eckelt, Daniel; Friebe, Milena; Gausemeier, Jürgen (Proceedings of the 27th ISPIM Innovation Conference, 19. - 22. Jun. 2016 International Society for Professional Innovation Management (ISPIM))

Perspective on the design of a decision support system based on Linked Data for process planning - Rehage, Gerald; Joppen, Robert; Gausemeier, Jürgen (Procedia Technology)

Intelligent Production System Planning with Virtual Design Reviews - Köchling, Daniel; Berssenbrügge, Jan; Schluessler, Joel; Stöcklein, Jörg (Proceedings of 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering (SysInt) 2016, Band 26)

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Journal of Computing and Information Science in Engineering, Band 16(3))

Advanced Traffic Simulation Framework for Networked Driving Simulators - Abdelgawad, Kareem; Henning, Sven; Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (AAC2016 (IFAC), 8th IFAC Symposium on Advances in Automotive Control (AAC 2016))

Modeling Language for Value Networks - Schneider, Marcel; Mittag, Tobias; Gausemeier, Jürgen (25th International Association for Management of Technology Conference Proceedings, 25th International Association for Management of Technology Conference, Band 25)

Business Model Based Configuration of Value Creation Networks - Mittag, Tobias; Schneider, Marcel; Gausemeier, Jürgen (25th International Association for Management of Technology Conference Proceedings, Band 25)

Industrie 4.0 - Internationaler Benchmark, Zukunftsoptionen und Handlungsempfehlungen für die Produktionsforschung - Gausemeier, Jürgen; Klocke, Fritz; Dülme, Christian; Eckelt, Daniel; Kabasci, Patrick; Kohlhuber, Martina; Schön, Nico; Schröder, Stephan; Wellensiek, Markus

DESIGN OF A SELF-OPTIMISING PRODUCTION CONTROL SYSTEM - Köchling, Daniel; Gausemeier, Jürgen; Joppen, Robert; Mittag, Tobias (14th International DESIGN Conference)

Integrated and iterative systems engineering and software requirements engineering for technical systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Journal of Software Evolution and Process)
The development of software-intensive technical systems involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and a system model. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline-specific development to start, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived in previous work a systematic transition from MBSE to model-based software requirements engineering. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. In this paper, we extend this approach with support for subsequent process iterations and provide an algorithm for the automated steps. We illustrate the approach and perform a case study with an example of an automotive embedded system.

Strategische Produktplanung - Adaptierbare Methoden, Prozesse und IT-Werkzeuge für die Planung der Marktleistungen von morgen - Gausemeier, Jürgen; Ovtcharova, Jivka; Amshoff, Benjamin; Eckelt, Daniel; Elstermann, Matthes; Placzek, Markus; Wiederkehr, Olga

Value Network Design for Innovations - Kage, Martin; Drewel, Marvin; Gausemeier, Jürgen; Schneider, Marcel (Proceedings of the 5th ISPIM Innovation Forum)

Die sich selbst optimierende Lackieranlage - Iwanek, Peter; Kühn, Arno (Journal für Oberflächentechnik 3(56))

Detecting white spots in innovation-driven intellectual property management - Eckelt, Daniel; Dülme, Christian; Gausemeier, Jürgen; Hemel, Simon (International Society for Professional Innovation Management (ISPIM))

Musik - Edition – Medien: Detmolder Projekte Der Digitalen Musikwissenschaft - Richts, Kristina; Röwenstrunk, Daniel

Systematik zur innovationsorientierten Kompetenzplanung - Rübbelke, René

Intelligente Arbeitsvorbereitung in der Cloud - Rehage, Gerald; Isenberg, Florian; Reisch, Raphael-Elias; Weber, Jens; Jurke, Benjamin; Pruschek, Peter (wt Werkstattstechnik online (1/2-2016))
Auf dem Weg zu Industrie 4.0 wird die Arbeitsvorbereitung zunehmend von kognitiver Informationstechnik unterstützt. Der Beitrag präsentiert die bisherigen Ergebnisse des Forschungsprojekts „Intelligente Arbeitsvorbereitung auf Basis virtueller Werkzeugmaschinen“. Projektziel ist eine Cloud-Dienstleistungsplattform zur Reduzierung der Rüst- und Nebenzeiten durch eine intelligente Planung. Hierzu zählen unter anderem die Auswahl und Validierung alternativer Maschinen sowie die automatische Optimierung der Einrichtungsparameter durch verteilte Simulationen.

Instrumentarium für einen lösungsmusterbasierten Entwurf fortgeschrittener mechatronischer Systeme - Anacker, Harald